99 Hypertension or hypertrophic cardiomyopathy? using cardiovascular magnetic resonance imaging to unmask the great imitator. (May 2019) - Keteepe-Arachi, Tracey; Basu, Joyee; Malhotra, Aneil; Dassananyake, sohani; Miles, Chris; Patel, Rishi; parry-williams, gemma; Ensam, Bode; Khong, Teck Khong; Papadakis, Michael; Tome, Maite; Sharma, Sanjay; et al.
Abstract : Background: Structural cardiac adaptations caused by hypertension present a diagnostic challenge when differentiating from hypertrophic cardiomyopathy (HCM), using traditional imaging techniques such as echocardiography (echo). Cardiac magnetic resonance imaging (CMR) offers reproducible anatomical, functional quantification as well as myocardial tissue characterisation which discriminates between hypertension and HCM. Purpose: To identify hypertensive individuals with undiagnosed HCM using CMR imaging. Methods: 100 consecutive African Caribbean (AC) and Caucasian hypertensive patients underwent CMR at a tertiary centre dedicated blood pressure clinic (55% male, mean age 51 years). In keeping with ESC guidelines, end diastolic wall thickness (EDWT) ≥ 15mm identified individuals within the "grey zone" between hypertension and with a potential HCM diagnosis.19 individuals were referred on to the dedicated inherited cardiac conditions clinic for further evaluation. Four patients expressed a definitive LV phenotype and were diagnosed with HCM. CMR parameters were compared in three groups: Hypertensive (HTN), grey zone Hypertensive (GZH) and HCM. See figure 1 and table 1. Results: CMR demonstrated end diastolic wall thickness (EDWT) >11 mm in 50% of hypertensives. 73% of the referred patients were AC and all 4 HCM patients were also AC. All referrals demonstrated EDWTs ≥14mm, 9 (47%) demonstrated late gadolinium enhancement of which 3 (16%) had HCM. Three had asymmetrical septal hypertrophy – 2 were in the HCM cohort and one underwent endomyocardial biopsy confirming HTN. Left ventricular mass index (LVMI) was significantly higher in GZH compared to HTN (p<0.0001) and in HCM compared to HTN (p=0.0004). EDWT was significantly greater in GZH compared to HTN (p<0.0001) and in HCM compared to HTN (p=0.0002). There was no significant difference in these parameters between GZH and HCM. See figure 1 and table 1. Conclusion: This study reports a 4% prevalence of HCM among hypertensive patients - 20 × greater than in the general population - which would not be diagnosed using echo alone. Screening hypertensive individuals with CMR is not yet routine but we advocate its use in these individuals especially in those of AC ethncitiy and in those in the "grey zone", to identify undiagnosed HCM, which has significant implications for lifestyle modification and family screening. Conflict of Interest: none